GAMBARAN HITUNG JUMLAH TROMBOSIT PADA PENDERITA DIABETES MELITUS TIPE 2 DI WILAYAH KERJA PUSKESMAS JEMBATAN KECIL KOTA BENGKULU - Tedy Febriyanto; Halimah, Halimah; Muhammad Geo (Jurnal Cakrawala Ilmiah, 2025)
Type 2 Diabetes Mellitus (T2DM) is a chronic metabolic disease characterized by hyperglycemia due to impaired insulin secretion or resistance. One common complication includes hematological abnormalities, such as changes in platelet count and function. This study aimed to describe the platelet count in T2DM patients as an early detection of complications. Methods: This descriptive quantitative study involved 39 T2DM patients from the Puskesmas Jembatan Kecil, Bengkulu City, selected through accidental sampling. Venous blood samples were analyzed using the Rayto RT-7600 Hematology Analyzer, and data were processed using univariate analysis. Results: The majority of respondents (89.7%) had platelet counts within the normal range (150,000–400,000/mcL), 2.5% had thrombocytopenia, and 7.6% had thrombocytosis. Most respondents were over 35 years old (97.5%), 66.6% had been diagnosed for less than five years, 46.1% had other complications, and 56.4% were female.Conclusion: Most T2DM patients had normal platelet counts, but a small proportion showed abnormalities. Routine laboratory evaluation is essential for early detection and prevention of complications, and platelet function assessment is recommended even when counts are within normal range